Reliability estimation of Weibull Lomax distribution via Bayesian approach - Arun Kumar Rao; Himashu Pandey (Memoirs of the Scientific Sections of the Romanian Academy, 2023)
Weibull Lomax distribution is considered. Bayesian method of estimation is employed in order to estimate the reliability function of Weibull Pareto distribution by using non-informative and beta priors. In this paper, the Bayes estimators of the reliability function have been obtained under squared error, precautionary and entropy loss functions.